Contestation of Power and Identity in the Dayak Tomun Indigenous Community in Central Kalimantan, Indonesia - Yogi, Ida Bagus Putu Prajna; Wijaya, I Nyoman; Darma Putra, I Nyoman; Suardiana, I Wayan (Jayapangus Press, 2025)
This study addresses the problem of identity ambivalence experienced by the Dayak Tomun community in Central Kalimantan as a result of interactions between customary tradition, Protestant Christianity, and state cultural policy. The research aims to explain how indigenous identity is shaped, contested, and negotiated within these intersecting power frameworks. Using a qualitative approach and cultural studies perspective, the analysis integrates Michel Foucault’s concept of disciplinary power, Pierre Bourdieu’s habitus and symbolic capital, and Anthony Giddens’ structuration theory. The findings show that Hidup Baadat and Mati Bapati (Living by Custom and Dying by Custom) are not merely ancestral customs, but disciplinary cultural practices that shape subjectivity and social conduct. The spread of Christianity introduced new moral and ritual regimes, generating tensions in the continuity of customary authority. Meanwhile, state intervention through Law No. 5/2017 on the Advancement of Culture redefined customary practices as cultural resources for development and tourism. This process results in identity ambivalence: traditional rituals continue to be performed, yet are simultaneously reframed as cultural commodities. The study offers a multi-theoretical interpretation of indigenous identity formation by demonstrating how disciplinary power, habitus, and structuration operate together in shaping the contemporary dynamics of Tomun cultural life.